Re: trailer trash. 1 - Villaire, Alyssa (Vault Comics, 2026)
Tabitha Moore has lived a miserable life of regret and being treated as "Trailer Trash Tabitha." But, after a mishap with an MRI, her mind is sent back to 1998 and into her 16-year-old body. With her life now in front of her, maybe this is the chance to redo it! But is it so easy to change what you've already lived through?--Back cover.